A biological melange and a peculiar led light could be a thaumaturgic approach to defeat manifold types of folliculitis in man and woman - Lorenzo Martini (Our Dermatology Online, 2017)
Nowadays PTD (photodynamic therapy) together with methyl aminolevulinate (MAL) pomades seem to be the goal and merit of all the vanguard dermatologists and aesthetic surgeons, who are determined to struggle radically the problems of folliculitis, malaise that disturbs men and women, even by the social point of view. In this study We attempt to treat 12 different cases of folliculitis caused by symptoms of different etiologies in men, women and in a transvestite, but not operate (idest a pre-op trans), using a cosmetic formula made of a particular fermented rice starch and particular irradiation for different quantities of time, depending on the gravity of the disease to treat. Results are utterly satisfying.